2010
DOI: 10.1039/b925612a
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted metabolic profiling reveals potential biomarkers in myocardial infarction and its application

Abstract: Although some important biomarkers for myocardial injury have been identified, there still lacks a systematic view of the development and progression of myocardial infarction, including enzymatic regulation, metabolite levels, fluxes, etc., which are pivotal to elucidate the physiological mechanism of disease. Here we present an untargeted analytical approach based on gas chromatography coupled with mass spectrometry (GC-MS) to map the temporal metabolic profilings in blood sera of myocardial infarction rat mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 36 publications
1
32
0
1
Order By: Relevance
“…Our findings revealed that AngSc is correlated with serum levels of phenylalanine and tyrosine. Accordingly, the results of animal experiments 28 and human studies 29 indicate that myocardial infarction is associated with increased levels of phenylalanine. It could be hypothesized that the association of phenylalanine with the extent of atherosclerosis is influenced by high-grade oxidative stress.…”
Section: Discussionmentioning
confidence: 96%
“…Our findings revealed that AngSc is correlated with serum levels of phenylalanine and tyrosine. Accordingly, the results of animal experiments 28 and human studies 29 indicate that myocardial infarction is associated with increased levels of phenylalanine. It could be hypothesized that the association of phenylalanine with the extent of atherosclerosis is influenced by high-grade oxidative stress.…”
Section: Discussionmentioning
confidence: 96%
“…Though some biomarkers related to AMI have been identified using a metabolomics method in recent years (Zhang et al, 2009;Lv et al, 2010;Yao et al, 2010), the metabolites that changed in the early period of AMI had still not been investigated. To achieve a complete understanding of the metabolite profile associated with AMI in the early period, an AMI model using the left anterior descending coronary artery (LADCA) ligation method was adopted, and then the serum biomarkers were analyzed after 5 h of the heart operation using a metabolomic method.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, variation of BCAAs was strongly correlated with underlying disease such as diabetes and therapeutic intervention for CVD. For MI specific studies, rat models induced by coronary artery ligation or isoproterenol have been used to identify the metabolic alterations and clarify the pathophysiological mechanisms in MI [14][15][16]. However, few clinical models have been used in metabolomics approaches for MI.…”
Section: Introductionmentioning
confidence: 99%